Differences in livelihood satisfaction between ethnic groups after selling farmland for renewable energy power projects in Ninh Thuan province, Vietnam - Quang, Nguyen Ngoc (Frontiers in Sustainable Food Systems, 2025)
This research investigates the factors affecting livelihood satisfaction and differences between ethnic groups after selling farmland for renewable energy power projects in Ninh Thuan province of Vietnam. Quantitative data were collected through direct questionnaires from 294 households that sold land. Factor analysis and related tests were conducted to refine the scale and test the model; Structural equation modeling was conducted to assess the impact of factors on farmers' livelihood satisfaction and compare the model between the Kinh group and the ethnic minority group. The results show that for the Kinh, all aspects impact livelihood satisfaction, in which economic-financial capital and natural capital have a stronger impact; for the minority group, natural capital has the strongest impact, and physical capital and social capital have insignificant impacts. This result indicates that there is a need for individual solutions suitable for each group to promote livelihood satisfaction.